The Development of an Instructional Model for Enhancing Cognitive Skills Based on Thai Qualifications Framework for Higher Education for Undergraduate Students Rajabhat Universities - Boonma, Kantida; Chindanurak, Tweesak; Suwanjinda, Duongdearn; PonPok, Nasan (STOU Education Journal, 2025)
This research and development study with the following objectives: 1) to develop an instructional model for enhancing cognitive skills based on Thai Qualifications Framework for Higher Education for undergraduate students at Rajabhat Universities; and 2) to study the effectiveness of the developed instructional model. The research comprised two processes: The first process was to study and synthesize a conceptual framework of an instructional model by simple random sampling include 114 administrators and general education lecturers from Rajabhat Universities throughout the country were a questionnaire, and was development of the instructional model by studying of 34 undergraduate students at Suratthani Rajabhat University enrolled in the environment and quality of life development course obtained from cluster random sampling. For the second process, the study of the effectiveness of the developed instructional model of the undergraduate students at Suratthani Rajabhat University enrolled in the environment and quality of life development course. One class consisting of 33 students was randomly assigned as an experiment group and 30 students was assigned as a control group. The employed research instruments were learning management plans and cognitive skills intelligence test. Statistics employed for data analysis were the mean, standard deviation and t-test for independent and dependent sample. The research findings were: 1) the developed instruction model comprised 4 components: (1) the rationale; (2) the objective; (3) the learning management process which comprised 6 steps: (3.1) Motivation, (3.2) Exploration, (3.3) Construction and Elaboration, (3.4) Reflection, (3.5) Conclusion, and (3.6 Evaluation; and (4) the measurement and evaluation. and 2) the effectiveness of the instructional model, it was found that; cognitive skill of the experiment group were significantly higher than the counterpart scores of the control group; and the post-learning cognitive skills scores were significantly higher than their pre-learning counterpart scores at the .01 level of statistical significance.